An application of structural equation modeling with partial least squares to analyze life satisfaction by degrees of urbanization - Jose A. Sánchez-Martí; Miguel A. Esteban-Yago (Electronic Research Archive)
The objective conditions of people's lives have historically played a greater role than subjective perceptions. However, this trend is shifting, accompanied by an ongoing debate about life satisfaction and urbanization. This research has two objectives, the first is to test the hypothesis of the urban paradox. The second is to analyze the differences in the determinants of life satisfaction by urbanization levels. In order to determine the degrees of urbanization, a geographic grid was used to distinguish between rural, intermediate, and urban areas. In addition, a multi-group analysis in structural equation models with partial least squares was conducted to analyze the determinants of life satisfaction. The model has been developed using three general determinants: economic situation, health, and social relations, which has been applied to a case study of the Region of Murcia. The database used for this study includes 2462 samples. The population living in rural areas showed less life satisfaction. Regarding the determinants, it was found that health acts as a partial mediator of social relations. Differences were also observed in the intensity of the determinants according to the degree of urbanization. Thus, the degree of urbanization acts as a moderator of life satisfaction. This research is noteworthy because it provides valuable insights for guiding regional public policies.